Globoid Cell Leucodystrophy (Krabbe's Disease): Deficiency of Galactocerebroside β-Galactosidase - Suzuki, Kunihiko (1970)
Profound deficiency of a specific enzyme, galactocerebroside β-galactosidase, has been demonstrated in the brains, liver, and spleen of three patients with Krabbe's globoid cell leucodystrophy. The activity of this enzyme was normal in a variety of other cerebral diseases, including those with similarly devasted white matter. The lack of enzyme activity was not due to an inhibitor in the tissue, nor is it due to a shift in the pH optimum. The deficiency of galactocerebroside β-galactosidase as the primary enzymatic defect can account for the morphological and biochemical characteristics of this disease better than the previously reported deficiency of cerebroside-sulfatide sulfotransferase.